ANALISIS KESALAHAN MULTIREPRESENTASI SISWA DALAM MENYELESAIKAN SOAL KINEMATIKA GERAK LURUS DI SMKN 1 SINTANG - Jalaluddin, Muhammad Iqbal; Djudin, Tomo; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the multi-representation errors of students in solving straight motion kinematics problems at SMKN 1 Sintang. The research method used is descriptive comparative. A total of 65 grade X students of SMKN 1 Sintang who were taken intact from the population were included as the study sample. Data collection techniques used in this study are written measurement techniques and direct communication techniques (interviews). This study found the average percentage of errors of multi-representation students in solving straight motion kinematics problems by 84%. There were no significant differences in multi-representation errors among high, medium and low ability students. This study also found the cause of multi-representation errors, namely students are not accustomed to using multiple representations in solving problems, low understanding of concepts and forgetting concepts in the material. Seeing these problems, the teacher needs to give problem training and train students to use multi-representation in learning, especially when solving questions and providing motivation to students both inside and outside the learning activities.Â Keywords: Multi-representation Error Analysis, Solving Problem, Straight Motion Kinematics